2011
DOI: 10.4276/030802211x13153015305556
|View full text |Cite
|
Sign up to set email alerts
|

The Lived Experience of Australian Retirees: ‘I'm Retired, What Do I Do Now?’

Abstract: The purpose of this qualitative study was to explore the lived experience of retirement in a context where it is not compulsory, and to understand consequent changes in roles, identity and occupational adaptation from the perspective of Australian retirees. Method: Five people aged between 61 and 68 years, who had retired during the previous 18 months, were interviewed. Data analysis included transcription and coding of data, data aggregation and identification of themes. Findings: The themes that emerged from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 29 publications
3
26
0
Order By: Relevance
“…This dual theme also emerged in Finnish magazines targeted at readers above 50 years (Lumme‐Sandt, ), and prime time TV in Germany (Kessler, Schwender, & Bowen, ). Similar themes have been found in both qualitative studies that interviewed retirees (Pepin & Deutscher, ), and quantitative ones, such as the Hartford Retirement Survey ().…”
supporting
confidence: 69%
“…This dual theme also emerged in Finnish magazines targeted at readers above 50 years (Lumme‐Sandt, ), and prime time TV in Germany (Kessler, Schwender, & Bowen, ). Similar themes have been found in both qualitative studies that interviewed retirees (Pepin & Deutscher, ), and quantitative ones, such as the Hartford Retirement Survey ().…”
supporting
confidence: 69%
“…Use of a process to gradually transition from a work-toretirement lifestyle to assist in adapting to retirement Includes: gradually reducing work hours and responsibilities (Pepin & Deutscher, 2011;Wiseman & Whiteford, 2007Wythes & Lyons, 2006); maintaining established connections (people and places) while establishing new connections (Wiseman & Whiteford, 2007 Financial Financial planning for retirement…”
Section: Gradual Transitionmentioning
confidence: 99%
“…Includes: understanding what to do and who to consult (Pepin & Deutscher, 2011) Interests and activities Includes: continuing to attend events where work-related activities previously occurred (Wiseman & Whiteford, 2009); continuing to engage in activities related to past paid work roles and skills (Hillman & Chapparo, 2002). May be a positive (e.g.…”
Section: Gradual Transitionmentioning
confidence: 99%
“…Peppin and Deutscher (2011) identified that older adults want to make choices about occupations, and for them to match their interests. Engagement in occupation, as in this project, may provide individuals with occupational roles and help to construct and maintain identity.…”
Section: Development Of Personal Resourcesmentioning
confidence: 99%
“…Many theorists present concepts of occupation and activity to help understand health in older adulthood (Cohen 2009, Law and McColl 2010, Peppin and Deutscher 2011. Although there has been discussion within the occupational therapy literature concerning terminology (Golledge 1998a, 1998b, Pierce 2001, the term 'occupation' as used in this paper refers specifically to the occupation of 'musicking', defined as: 'to take part, in any capacity, in a musical performance, whether by performing, by listening, by rehearsing or practising, by providing material for performance' (Small 1998, p9).…”
Section: Literature Review Occupation In Later Lifementioning
confidence: 99%